Functional properties of Lactobacillus strains isolated from dairy products - Bujňáková, Dobroslava; Kmeť, Vladimír (Folia microbiologica, 2012)
Twenty-four acid- and bile-tolerant lactobacilli isolates from dairy products were identified and further in vitro characterized for the presence of functional traits potentially useful for probiotic applications, which included desirable and undesirable traits, such as biofilm formation, ability to inhibit intestinal pathogens, antibiotic susceptibility, and enzyme activity. The majority of examined strains were susceptible to certain antimicrobial agents (streptomycin, gentamicin, clindamycin, erythromycin, tetracycline, quinupristin-dalfopristin), except for three strains of Lactobacillus rhamnosus with minimal inhibitory concentration levels for streptomycin higher than the microbiological breakpoints (≥32 μg/mL), which are considered as resistant. Undesirable traits such as α-chymotrypsin or N-acetyl-β-glucosaminidase activities were not detected, but low β-glucuronidase, and moderate and high β-glucosidase activities were recorded in nine strains, which were eliminated from further examination together with three isolates showing unsuitable antibiotic resistance. Of the remaining 12 isolates, 4 (Lactobacillus fermentum 202, Lactobacillus gallinarum 7001, L. rhamnosus 183, and Lactobacillus plantarum L2-1) manifested an outstanding potential to inhibit selected intestinal pathogens in an agar spot test, including Escherichia coli and Salmonella spp., and simultaneously demonstrated strong biofilm-forming capacity. In conclusion, the results of our in vitro experiments showed that the above four strains had a potential probiotic value and met the criteria to be identified as a possible probiotic microorganism, with the necessity of verification through well-designed in vivo experimental, clinical, and technological studies before the strains can be used as probiotics or as starter probiotic cultures.
Keywords: mléko; Anti-Bacterial Agents; ovce; biofilmy; probiotika; skot; Cheese; Probiotics; Bacterial Proteins; sýr; zvířata; Biofilms; antibakteriální látky; Cattle; Milk; Sheep; bakteriální proteiny; Lactobacillus; Animals